Role of Sphingolipids in the Pathobiology of Lung Inflammation - Riccardo Ghidoni; Anna Caretti; Paola Signorelli (Hindawi Limited, 2015)
Sphingolipid bioactivities in the respiratory airways and the roles of the proteins that handle them have been extensively investigated. Gas or inhaled particles or microorganisms come into contact with mucus components, epithelial cells, blood barrier, and immune surveillance within the airways. Lung structure and functionality rely on a complex interplay of polar and hydrophobic structures forming the surfactant layer and governing external-internal exchanges, such as glycerol-phospholipids sphingolipids and proteins. Sphingolipids act as important signaling mediators involved in the control of cell survival and stress response, as well as secreted molecules endowed with inflammation-regulatory activities. Most successful respiratory infection and injuries evolve in the alveolar compartment, the critical lung functional unit involved in gas exchange. Sphingolipid altered metabolism in this compartment is closely related to inflammatory reaction and ceramide increase, in particular, favors the switch to pathological hyperinflammation. This short review explores a few mechanisms underlying sphingolipid involvement in the healthy lung (surfactant production and endothelial barrier maintenance) and in a selection of lung pathologies in which the impact of sphingolipid synthesis and metabolism is most apparent, such as acute lung injury, or chronic pathologies such as cystic fibrosis and chronic obstructive pulmonary disease.